Area and International Studies in Turkey: The Case of the United States - Turan, Ilter (Center Foreign Policy & Peace Research, 2012)
Area studies in the international relations discipline have evolved in response to specific needs of countries and particular conditions of the world affairs at a given time. This article addresses a set of conditions and needs that influenced the development of area studies in international relations with a focus on the emergence and growth of studies on the United States in Turkey. Accordingly, it is argued that Turkey has historically conceptualized external relations as state-to-state relations and not prioritized initially a research program on area studies. However, the shift from import substitution to export-led growth and the end of the Cold War created an environment in which Turkey's needs to research about other societies have intensified. This has led to the establishment of research programs and centers at universities as well as the opening of think tanks, some funded by the public, others privately. In light of the assessment of the growth of these research and teaching institutions focusing on the United States, it is concluded that American studies are less developed than what might be expected given Turkey's close relationship with the United States. Some explanations are also offered for such an observation.
Keywords: Area Studies; Foreign Policy; Research Centers; Think Tanks; United States; Turkey